Multimodal electron microscopy of halide perovskite interfacial dynamics - Xinjuan Li; Qichun Gu; Wei Huang; Simon M. Fairclough; Richard H. Friend; Samuel D. Stranks; Tianjun Liu; Caterina Ducati (Nature, 2026)
Abstract Halide perovskite light-emitting diodes promise high-efficiency 1–3 , low-cost optoelectronics, yet their operational instability remains a critical barrier to practical deployment. Here we develop a multimodal in situ electron microscopy approach that integrates four-dimensional scanning transmission electron microscopy, energy-dispersive X-ray spectroscopy and atomic-resolution imaging to directly visualize structural and chemical evolution in a working halide perovskite light-emitting diode with nanometre precision. Our in situ biasing measurements uncover nanoscale structural and chemical transformations initiated at transport layer interfaces, including the formation of metallic lead and lead-rich secondary phases, as well as strain-driven grain fragmentation. On biasing, we observe the partial transformation of the metallic Al contact to insulating AlCl 3 . Crucially, whereas the bulk of the perovskite emitter remains relatively intact, our experiment shows that degradation is localized at interfaces. By comparing in situ and ex situ measurements, these results establish a mechanistic link between interfacial strain, ionic transport and electrochemical reactions in working devices, and provide a broadly applicable framework for nanoscale degradation analysis in complex multilayered optoelectronic systems using multimodal in situ biasing microscopy.